Research on and Application of Blasting Excavation Technology for Highway Cutting Under Complex Environment. Issue 1 (November 2020) - Huang, Xiqin; Zhang, Xiaojun; Sun, Junshan; Hao, Haigang; Bai, Rongshuai
Abstract: Blasting construction is currently a relatively quick and efficient method of earthwork excavation, but harmful effects such as vibration and flying stones caused by blasting are an important issue that cannot be ignored. Presplitting blasting is an important construction method to control blasting vibration and protect adjacent buildings (structures). This article takes the pre-split blasting of the cutting near the beacon tower in Yangcheng Village as an example. From the discussion of blasting design and blasting effect analysis, the research on pre-split blasting is carried out. It has important reference significance for the design of similar blasting projects.